UJI PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI TERKAIT DENGAN WORK ABILITY, WORK ENVIRONMENT, DAN JOB SATISFACTION DI PT. RATIO KARUNIA MULYA GARMENT KARANGANYAR - Hendarti, Yanita (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aimed to determine the effect of work ability, work environment and job satisfaction on employee productivity PT. Ratio Karunia Mulya Garment Karanganyar. Sample size of 100 respondents defined using census method. As independent variables, namely the ability to work, work environment and job satisfaction, while the dependent variable is employee productivity. The analysis used include validity, reliability test, descriptive analysis, the classical assumption test, multiple linear regression analysis, significance testing and hypothesis testing. Questionnaire data were analyzed using Ordinary Least Square (OLS) so that it can be seen that there is a simultaneous significant influence between variables work ability, work environment, and job satisfaction on employee productivity at PT. Ratio Karunia Mulya Garment Karanganyar, but no significant effect variables employability and job satisfaction on employee productivity. No significant influence on the work environment variables on labor productivity of the research looked primarily at the cleanliness of the work environment indicators.Keywords: Ordinary Least Square, Job Satisfaction, Work capacity, work environment, work productivity